The Effect of Ethanol on the Fetal Heart Muscle - Galina Zhanaidarova (Journal of Global Pharma Technology, 2020)
The survey goal was to study the effect of antenatal intoxication with ethanol on embryogenesis of the fetal cardiac muscle. The experiment was conducted on 48 female rats weighing 180-200 grams. To study the embryotoxic effect of ethanol, 2 groups were created. In group I, 18 rats throughout the pregnancy received a 15% ethanol solution daily instead of water. 18 animals of the control group were kept under normal vivarium conditions. On the 13th, 18th and 21st day of pregnancy, the females were killed, removed from the cauls of living fetuses, their length, body weight and heart weight were measured.Histological preparations stained with hematoxylin and eosin were prepared from the hearts of the fetuses. The nuclear cytoplasmic ratio, capillarydensity of the capillary network and cardiomyoblasts, procardiomyocytes and cardiomyocytes were measured. The data obtained were statistically processed. In group II, 6 animals during pregnancy (from 6 to 21 days) were injected daily with an endogastric solution of 30% ethanol at a dose of 5 g / kg of body weight, and 6 animals of the control group received physiological salt solution in equivalent amounts.On the 18th day of pregnancy, the females were killed, the material taken (cardiac muscle of the fetus) was studied by electron microscopy. Our study showed that antenatal intoxication with ethanol has a pronounced embryotoxic effect on the heart muscle, which manifests itself at the cellular and subcellular levels. The value of the obtained results lies in the fact that for the first time at the electron microscopic level, ultrastructural changes in the fetal cardiac muscle during prenatal intoxication with ethanol are shown. Keywords: Fetal alcohol spectrum disorder, Cardiac muscle, Electron microscopy.